Eating disorders in pregnancy - Kníže, M; Baraníková, Z; Krejčová, V; Fait, T (Ceska gynekologie, 2018)
OBJECTIVE: To highlight a problem of eating disorders in pregnancy and the need for interdisciplinary cooperation in these cases. DESIGN: Case report. SETTING: Department of Gynecology and Obstetrics, 2nd Faculty of Medicine, University hospital Motol, Prague. CASE REPORT: We report the course of pregnancy in a 19-year-old woman with an atypical form of mental anorexia. The patient was repeatedly hospitalized for metabolic disruption. The pregnancy was finally terminated at the 27th week of pregnancy for fetal growth restriction of the fetus. CONCLUSION: Despite the frequent irregularities of the menstrual cycle in eating disorders, a spontaneous conception is possible. The prognosis of pregnancy is uncertain and may endanger the mother and fetus. Management of pregnant women with eating disorders requires the cooperation of a perinatologist, internist, nutritional therapist, psychiatrist or psychologist.
Keywords: potrat léčebný; mental anorexia; Abortion, Therapeutic; Fetal Growth Retardation; bulimia; výsledek těhotenství; Pregnancy; Humans; amenorrhoea; Female; mladý dospělý; Pregnancy Outcome; lidé; poruchy příjmu potravy; Pregnancy Complications; fetal growth restriction; ženské pohlaví; fetal growth restriction amenorrhoea.; pregnancy; růstová retardace plodu; těhotenství; Feeding and Eating Disorders; Young Adult; komplikace těhotenství